2021
DOI: 10.3389/fvets.2020.608901
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Recovery of Nosocomial Bacteria in a Companion Animal Shelter Before and After Infection Control Procedures

Abstract: While the effects of cleaning and disinfection practices on the reduction of environmental nosocomial bacteria are well-established in human and large animal veterinary hospitals, how animal movements within animal health care facilities influence environmental bacterial recovery is poorly understood. During three consecutive weeks, 155 electrostatic wipes were collected from the environment pre- and post-cleaning only or following disinfection from seven target locations within an animal shelter. All samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…ARM-positive samples were commonly retrieved from areas with no patient contact, such as the kitchen, the laboratory, and the toilets. In a recent study conducted at a companion animal shelter, these areas were reported to have a high bacterial contamination [ 35 ]. Thus, areas with little to no patient contact in a veterinary clinic could pose a reservoir for ARM and a focus should also be placed on these locations when implementing cleaning and disinfection protocols.…”
Section: Discussionmentioning
confidence: 99%
“…ARM-positive samples were commonly retrieved from areas with no patient contact, such as the kitchen, the laboratory, and the toilets. In a recent study conducted at a companion animal shelter, these areas were reported to have a high bacterial contamination [ 35 ]. Thus, areas with little to no patient contact in a veterinary clinic could pose a reservoir for ARM and a focus should also be placed on these locations when implementing cleaning and disinfection protocols.…”
Section: Discussionmentioning
confidence: 99%
“…P. aeruginosa has been previously listed as a concern for transmission in small animal clinics with challenges highlighted as lesser patient compliance and hygiene (Stull and Weese, 2015). The bacterium was repeatedly isolated from bedding and the veterinary clinical environment before and after infection control intervention at a dog shelter (Horsman et al, 2020). The presence of P. aeruginosa in the surrounding environment and the data regarding transmission of P. aeruginosa in certain settings (Fothergill et al, 2012) may mean that the bacterium could be transmitted horizontally between susceptible animals (those with a breach to normal defence barriers or underlying health issues) in certain settings, such as veterinary inpatient facilities or homes with multiple animals/animal shelters.…”
Section: Routes Of Transmissionmentioning
confidence: 99%